The Psychophysiological Effects of Different Tempo Music on Endurance Versus High-Intensity Performances - Patania, Vittoria Maria; Padulo, Johnny; Iuliano, Enzo; Ardigò, Luca Paolo; Čular, Dražen; Miletić, Alen; De Giorgio, Andrea (Frontiers in Psychology, 2020)
The use of music during training represents a special paradigm for trainers to stimulate people undertaking different types of exercise. However, the relationship between the tempo of music and perception of effort during different metabolic demands is still unclear. Therefore, the aim of this research was to determine whether high intensity exercise is more sensitive to the beneficial effects of music than eendurance exercise. This study assessed 19 active women (age 26.4 ± 2.6 years) during endurance (walking for 10’ at 6.5 km/h on a treadmill) and high intensity (80% on 1-RM) exercise under four different randomly assigned conditions: without music (NM), with music at 90 - 110 bpm (LOW), with music at 130 - 150 bpm (MED) and with music at 170 - 190 bpm (HIGH). During each trial, heart rate (HR) and the rating of perceived exertion (RPE) were assessed. Repeated analysis of variance measures was used to detect any differences between the four conditions during high intensity and low intensity exercise. RPE showed more substantial changes during the endurance exercises (11%,) than during high intensity exercise (6.5%,) between HIGH and NM conditions. The metabolic demand during the walking exercise increased between NM and HIGH bpm conditions. This study indicates the benefits of music under stress conditions as well as during endurance and high intensity training. The results demonstrate that the beneficial effects of music are more likely to be seen in endurance exercise. Consequently, music may be considered an important tool to stimulate people engaging in low intensity physical exercise.